ANALISIS PENCAMPURAN BATUBARA PADA PT. BUKIT ASAM TBK DALAM UPAYA MENINGKATKAN KUALITAS BATUBARA UNTUK MEMENUHI KRITERIA PERMINTAAN PLTU BUKIT ASAM TANJUNG ENIM, SUMATERA SELATAN - Fitriani. A; Zahar, Wahyudi; El Hakim, Muhammad (Jurnal Teknologi Mineral dan Batubara, 2024)
PT. Bukit Asam Tbk provides BA 50 type coal to be sent to the Bukit Asam Tanjung Enim PLTU. The aim of this research is to obtain coal that suits the needs of the Bukit Asam Tanjung Enim PLTU. The method used is to simulate the blending of several types of coal at PT. Bukit Asam Tbk such as mine brand AL 49, mine brand AL 51, mine brand AL 53 and mine brand AL 55. The blending method uses the stack arrangement method with the layer arrangement method using the layered method. The research results show that the blending  simulation consists of 11 types of blending, four of which cannot be used as recommendations because they have a higher calorific value than BA 50. Of the seven recommended simulations, the AL 49 AL 51 simulation has the highest profit price value compared to the agreed selling price, namely $0.38 per ton and $1,157.55 per day or equal to IDR 18,216,357.16 per day. In this research, it is not only recommended to blend coal with two types of coal of different qualities, but innovation is carried out by blending which can be done with more than two types of coal of different qualities.